2000
DOI: 10.1515/zna-2000-1-245
|View full text |Cite
|
Sign up to set email alerts
|

Quadrupole Interaction in Ternary Chalcopyrite Semiconductors: Experiments and Theory

Abstract: Electric field gradients have been measured at substitutional lattice sites in ternary semiconductors using Perturbed γ -γ Angular Correlation spectroscopy (PAC). The experimental results for AIBIIIC2 chalcopyrite structure compounds and • AIIB2IIIC4IV defect chalcopyrites are compared with ab nitio calculations. The latter were carried out with the WIEN code that uses the Full Potential Linearized Augmented Plane Wave method within a density functional theory. The agreement between experiment and theory is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Reprinted with permission Razzetti et al [11]. © 1987, Elsevier On the other hand, the temperature-induced order-disorder transitions were investigated in A II B III 2 X VI 4 compounds [18][19][20]. In analyzing these data it was observed that the lower the δ the higher the temperature of the order-disorder transition.…”
Section: Fig 11 Grimm-sommerfeld Splitting Diagram For Tetrahedral mentioning
confidence: 99%
See 1 more Smart Citation
“…Reprinted with permission Razzetti et al [11]. © 1987, Elsevier On the other hand, the temperature-induced order-disorder transitions were investigated in A II B III 2 X VI 4 compounds [18][19][20]. In analyzing these data it was observed that the lower the δ the higher the temperature of the order-disorder transition.…”
Section: Fig 11 Grimm-sommerfeld Splitting Diagram For Tetrahedral mentioning
confidence: 99%
“…1.1, a simple relationship was suggested there between the c/a ratio and the cation sublattice ordering: the orderdisorder transition with increasing temperature occurs only in chalcopyrites with axial ratio c/a > 1.95. As concerns defect chalcopyrite A II B III 2 X VI 4 compounds, it was found that order-disorder transitions can occur with increasing temperature in materials with δ > 0.05 as well [18][19][20].…”
Section: Trends In Temperature-and Pressure-induced Phase Transitionsmentioning
confidence: 99%